A Crash in the dark - Flight, Colette; Blum, Edward; Nettles, John (Disaster (Television program), 1996)
This programme looks at the collision between two high speed trains at the Wales end of the Severn Tunnel on Dec. 7, 1991. It discusses how a "failsafe" system failed, due to a combination of poor design, equipment failure and human error. At the time of filming, many of the safety measures recommended by the subsequent inquiry had still not been implemented.